Strategic environmental assessment in conjunction with assessment of impacts on environment - Bojko, Tatyana; Dzhygyrey, Iryna; Abramova, Alla; Skladannyy, Denys (Lviv Politechnic Publishing House, 2017)
The tool for supporting the strategic environmental assessment of large-scale territorial entities’ and urban ecosystems’ development projects is presented In the paper. The concept of environmental impact assessment is used for the development of this tool. The use of the industrial objects’ ecological risk indicators for environmental safety estimation is suggested.
Keywords: strategic environmental assessment; assessment of impacts on environment; environmental risk